Metformin attenuates TBHP-induced oxidative injury in human lens epithelial cells and is associated with SIRT1/FOXO1-related autophagy - Zhuxuan Yan; Wei Chi; Zhenguo Yan; Hanrui Wang (PLoS ONE, 2026)
Metformin (MET), a first-line antidiabetic drug, has been increasingly implicated in cellular protection under oxidative stress, yet its mechanisms in lens epithelial cells (LECs) remain incompletely defined. Using a tert-butyl hydroperoxide (TBHP)-induced acute oxidative injury model in human HLE-B3 cells, we investigated whether SIRT1/FOXO1-related autophagy contributes to MET-associated cytoprotection. MET pretreatment reduced intracellular reactive oxygen species, preserved antioxidant defenses, improved cell viability, and decreased apoptosis after TBHP challenge. MET also enhanced autophagy markers and, under lysosomal blockade with chloroquine or bafilomycin A1, showed LC3-II/p62 changes consistent with increased autophagic flux. Pharmacologic inhibition of SIRT1 (EX-527) or early-stage autophagy (3-methyladenine) partially attenuated MET-associated improvements across oxidative stress and survival endpoints, supporting a role for SIRT1/FOXO1-related autophagy in this response. Although limited to an in vitro setting and pharmacological perturbation, these findings suggest that MET may mitigate oxidative injury in lens epithelium, highlighting SIRT1/FOXO1-autophagy as a potential pathway relevant to oxidative stress processes in cataractogenesis.